The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/mmy/myz116
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and natural compounds for the treatment of dermatophytosis

Abstract: Dermatophytes are a group of pathogenic fungi that exclusively infect the stratum corneum of the skin, nails, and hair, causing dermatophytosis. Superficial skin infections caused by dermatophytes have increased in the last decades. There are conventional antifungals that treat these infections, such as terbinafine, fluconazole, and others. However, the limitations of these treatments (resistance, side effects and toxicity) along with the increasing over-prescription, the misuse of these antifungals and the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
0
10
0
2
Order By: Relevance
“…Conventional antifungal drugs used in dermatophytosis such as terbinafine present difficulties, and resistance of dermatophytes has been increasingly reported, which leads to the search for new natural, alternative antifungals (Lopes et al 2019). In this context, the antifungal activity of monoterpenes against pathogenic dermatophytes was evaluated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional antifungal drugs used in dermatophytosis such as terbinafine present difficulties, and resistance of dermatophytes has been increasingly reported, which leads to the search for new natural, alternative antifungals (Lopes et al 2019). In this context, the antifungal activity of monoterpenes against pathogenic dermatophytes was evaluated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that such compounds are lipophilic and have a small molecular size which enable their passive diffusion through fungi membranes [16]. Volatile compounds exert their fungicidal activity through different mechanisms of action that include, among others, the perturbation of the lipid membrane organization [60] followed by the increased permeability of the fungal cell wall/membrane, the extravasation of cell constituents, the inhibition of ergosterol synthesis, and cell lysis [15,23]. Moreover, it was reported that several main constituents of the Apiaceae EOs included in our study acted on the virulence factors and resistance mechanisms of T. rubrum.…”
Section: Discussionmentioning
confidence: 99%
“…Distillation or pressing are physical processes used to obtain EOs, which comprise a blend of small volatile molecules that act as signaling agents in plants (e.g., attraction of pollinators, antifeedant agents, and protection against microorganisms) [21,22]. The antidermatophytic propensities of EOs are also well-documented and include the disruption of the cell wall/membrane; the inhibition of spore germination, ergosterol and cellular proteins synthesis; efflux pumps, and biofilm formation [23,24]. Moreover, EOs exhibit anti-inflammatory effects, thus supporting lesion healing and alleviating symptoms related to dermatophytosis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Triazoles inhibit sterol 14-α-demethylase, and allylamines inhibit squalene epoxidase, the inhibition of both enzymes leading to inhibition of ergosterol biosynthesis. Allylamines also lead to the accumulation of lanosterol, a toxic intermediary compound of the ergosterol biosynthesis pathway [8][9][10]. Terbinafine, which acts as a fungicide, is the drug of choice against Trichophyton spp.…”
Section: Introductionmentioning
confidence: 99%